Islam and Human Rights in the Perspective of the Qur'an: A Thematic Interpretive Study: Islam dan Hak Asasi Manusia Dalam Perspektif Al-Qur’an: Kajian Tafsir Tematik - Elisa Sasmita; Elshadra Righayatsyah; Asep Abdul Muhyi (Bulletin of Islamic Research, 2024)
Human rights are rights that must be obtained by every human being, regardless of social status. The Qur'an contains the concepts of human rights. This article describes the rights of individuals in accordance with the concept of human rights in Islam, referring to the verses of the Qur'an and the concept of maqasid shari'ah which are five: hifz al-din, hifz al-mal, hifz al-nafs, hifz al-aql, and hifz al-nasl. The approach used in this research is tafsir maudhu'i, by collecting and interpreting related verses, as well as including asbab an-nuzul verses and their Munasabah. The results show that Islam recognizes human rights as inherent in every human being, not as a gift from society, but as part of human nature. The concept of human rights in Islam is based on the theocentric principle, where all rights are bound to the will of God. Although there is debate about the implementation of human rights in the context of Islamic law, Islam emphasizes the importance of respecting and valuing fellow human beings by safeguarding five human rights: freedom, life, equality, protection of property, and justice. In conclusion, Islam teaches the protection and respect for human rights to maintain human welfare, although there are differences with the modern concept of human rights. This research highlights the importance of maintaining human rights principles in the context of a just and dignified social life.